Pelatihan Pemanfaatan Stik Es Krim Sebagai Alternatif Dekorasi Dinding Rumah - Suprianingsih Suprianingsih; Desipriani Desipriani; Yahya Tanjung; Saslika Febrianti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research focuses on the utilization of ice cream sticks as an alternative material for wall decoration. The objective of this study is to enhance the creativity of participants, provide an economical solution for home decoration, increase awareness of the use of recycled materials, and explore new economic opportunities. The training program developed in this research aims to teach participants how to create aesthetically pleasing and unique wall decorations using ice cream sticks, a commonly available and inexpensive material. The training includes theoretical and practical sessions to ensure participants gain both knowledge and hands-on experience. The results show that participants not only developed new skills but also gained insights into potential business opportunities in the craft industry. Additionally, this study contributes to environmental sustainability by promoting the use of recycled materials. The findings suggest that with proper guidance and training, ice cream sticks can be effectively transformed into valuable decorative items, thereby offering both economic and environmental benefits.